Rooting of two types of cuttings of fruit crops vaccinium floribundum kunth and disterigma alaternoides (kunth) niedenzu (ericaceae) (2011)
Vaccinium floribundum Kunth and Disterigma alaternoides (Kunth) Niedenzu are two fruit-bearing species of the family Ericaceae, natives of the Andean forest. Given very scarcem knowledge on their ecophysiology, it is not known how to propagate these plants, which limits the possibility of introducing these into the commercial culture. The present study had an objective to evaluate the rooting potential of softwood and hardwood cuttings of V. floribundum and D. alaternoides using 50-400 mg L-1 naphthaleneacetic acid (NAA) and indole- 3-butyric acid (IBA) as rooting hormones in an organic-mineral medium. The softwood cuttings taken from the apical part of the branch had up to 47.0% rooting in V. floribundum and up to 77.2% in D. alaternoides at day 60, whereas hardwood cuttings taken from the base of the branch presented lower rooting values, among 8.1 and 17.8% in V. floribundum and among 6.8 and 34.5% in D. alaternoides. Softwood cuttings of V. floribundum y D. alaternoides treated with 400 mg L-1 mg NAA remained viable up to 64 and 86%, while the rooting percentage was up to 44.4 and 77.2 %, and average number of roots was up to 8.4 and 6.3, respectively. The results of the study offer a base for development of the protocol for the vegetative propagation of these species